Avaliação do impacto da implantação do Custo Marginal da Operação - CMO semi-horário e Preço de Liquidação das Diferenças - PLD horário - Campanholo Filho, Braz (2024)
In the Brazilian Electric System - SEB, both in the operation and in the commercialization of energy, hydrothermal models are used to calculate the Marginal Cost of Operation - CMO - and the Difference Settlement Price - PLD. The CMO is calculated by the National System Operator – ONS - and is used to dispatch electrical energy generation. The PLD is calculated by the Electricity Trading Chamber – CCEE – and is used to settle operations not covered by energy contracts. Until 2019, both CMO and PLD were calculated weekly by load level and used throughout the following week. In 2020, the CMO started to be calculated daily, for every half hour of the following day. In 2021, the PLD also began to be calculated daily, for each hour of the following day. “Shadow” assessments carried out by ONS and CCEE indicated that the adoption of the new granularity would lead, among other benefits, to better representation of the load curve, reduction of generations outside the order of merit – GFOM and reduction of System Service Charges – ESS. The objective of this article is to evaluate whether the expected objectives regarding the reduction of GFOM and ESS were achieved, using data from the ONS and CCEE (from 2017 to 2022) before and after the adoption of the new granularity. As a result, we highlight that the implementation of the semi-hourly CMO reduced the GFOM by 527 averages (disregarding the amount for energy guarantee) and that no statistical evidence was found that the implementation of the hourly PLD reduced the ESS. The amount of reduction in GFOM could mean an average monthly reduction of around R$38 million, considering Unit Variable Cost – CVU of R$100.00/MWh, one of the lowest CVU values of thermal plants in the National Interconnected System - SIN. We highlight that the implementation of semi-hourly CMO did not have a statistically significant effect on the average monthly CMO in the period analyzed. Likewise, the implementation of the hourly PLD also did not have a statistically significant effect on the average monthly PLD in the period analyzed. We can also conclude that the water crisis and GFOM have a positive effect on the ESS, increasing SIN charges, as expected, considering the literature on this subject. We emphasize that in the period analyzed we had the effect of a pandemic in 2020 and a water crisis in 202.